Audit Delay: Firm Size, Solvability, And Profitability - Kenneth Davin H, Jonnardi (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to determine the effect of firm size, solvability, and profitability on audit delay on manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The independent variables in this research are firm size, solvability, and profitability. While the dependent variable is audit delay. The population of this research is 33 companies each year from manufacturing companies listed at Indonesia Stock Exchange in 2014-2018. The sampling method is by purposive sampling. In addition, the data analysis method used is analysis regression and descriptive statistics. The result of this research indicates that the firm size and profitability affect audit delay. While solvability has no effect on audit delay.